KONSEPSI ILMU DALAM KISAH NABI SULAIMAN DALAM AL QUR’AN - Mizwar, Edi; Syabuddin; Syahminan (Jurnal Tarbiyah Almuslim, 2024)
The problem in this research is how the concept of knowledge is portrayed in the story of Prophet Solomon in the Quran. The research adopts a qualitative approach and utilizes library research as the research method. Two types of data are used: primary data from the Quran regarding the concept of knowledge in the story of Prophet Solomon and secondary data from relevant books, journals, and Islamic texts. The data obtained are analyzed using descriptive methods.  The findings of the research reveal that the concept of knowledge in the story of Prophet Solomon in the Quran is evident in Surah An-Naml [27]: 15 and 16. These verses explain that Allah has bestowed wisdom and knowledge upon Prophet David and Prophet Solomon, encompassing knowledge related to God and His laws as well as general knowledge, such as the ability to lead and govern their people. They practice their knowledge well and express gratitude to Allah for the boundless blessings bestowed upon them. Moreover, Prophet Solomon is granted by Allah with additional virtues, including the ability to understand the sounds of birds and other creatures. The verses also elucidate that Allah has endowed Prophet Solomon with the capabilities and resources needed to govern his kingdom. Knowledge in the context of the story of Solomon serves prominent purposes, such as wisdom in governance, acknowledgment of Allah's power, submission to Allah's will, communication with nature, moral and ethical teachings, and obedience to Allah. The story of Solomon in the Quran involves various types of knowledge and learning, encompassing aspects such as creed, interpretation, monotheism, jurisprudence, miracles, history, leadership, language, theology, and ethics.